2012
DOI: 10.1177/0267659112438932
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Quadrox-i and Capiox FX neonatal oxygenators with integrated arterial filters in eliminating gaseous microemboli and retaining hemodynamic properties during simulated cardiopulmonary bypass

Abstract: Perfusion quality during cardiopulmonary bypass (CPB) procedures can contribute to postoperative neurological complications and influence patient recovery and outcome. Gaseous microemboli generated in the circuit and hemodynamic properties of blood reaching the patient can be monitored during CPB to optimize perfusion. Oxygenators that oxygenate the blood during CPB can significantly influence the quality of blood reaching the patient by their manufacturing designs. New hollow-fiber membrane oxygenators are de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 11 publications
3
19
0
1
Order By: Relevance
“…A linear mixed-effects model was fit to the continuous hemodynamic outcomes (e.g., MAP, THE) to compare cannula size (e.g., 8,10,12), tubing size (e.g., 1/4 and 3/16 inch), and temperatures (e.g., 28 and 35°C) within specific flow rates (9). The linear mixed-effects model is an extension of linear regression that accounts for the within-subject variability inherent in repeated measures designs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A linear mixed-effects model was fit to the continuous hemodynamic outcomes (e.g., MAP, THE) to compare cannula size (e.g., 8,10,12), tubing size (e.g., 1/4 and 3/16 inch), and temperatures (e.g., 28 and 35°C) within specific flow rates (9). The linear mixed-effects model is an extension of linear regression that accounts for the within-subject variability inherent in repeated measures designs.…”
Section: Discussionmentioning
confidence: 99%
“…All components of the CPB circuitry-oxygenator with or without an integrated arterial line filter, venous and cardiotomy reservoirs, arterial and venous cannulae and tubing-should be evaluated in vitro to determine their hydrodynamic performance before they are used in clinical practice (10)(11)(12)(13)(14)(15)(16). In the present study, the results demonstrated that the pressure drop of arterial line tubing was the main resistance in the simulated pediatric CPB circuits, except in circuit I (1/4 in ID) using 8 Fr arterial cannula at 500 mL/min and 10 Fr arterial cannula at 1000 mL/min.…”
Section: Discussionmentioning
confidence: 99%
“…The new generation hollow fiber membrane oxygenators with integrated arterial filters have replaced the separate arterial filters to reduce priming volume without losing filtration ability. Our in vitro studies showed that the integrated arterial filter minimally influences the hemodynamics of the circuit but that the GME capturing ability may be slightly affected, likely due to the different integrated GME filtering methods (9).…”
Section: Oxygenator With/without Iafmentioning
confidence: 89%
“…Therefore, it is necessary to independently evaluate the oxygenators on the market to select the best one before it is used for patients. We performed in vitro evaluations of several pediatric oxygenators, including those with and without an integrated arterial filter, in terms of the transmembrane pressure gradient, hemodynamic energy transmission, and gaseous microemboli (GME) handling ability (6)(7)(8)(9)(10). Oxygenators with lower priming volume, lower transmembrane pressure gradient, higher gas exchange efficiency, and higher GME capturing ability are recommended.…”
Section: Oxygenator With/without Iafmentioning
confidence: 99%
“…Снижение гемодилюционной анемии и увеличение ми-нимальной концентрации Hb приводят, в том числе, и к меньшей потребности использования вазопрессоров в те-чение перфузии [8,16]. Кроме того, некоторые авторы [17,18] отмечают уменьшение числа газовых микроэмбо-лов при использовании подобных оксигенаторов, что от-ражается на количестве послеоперационных неврологи-ческих осложнений второго типа.…”
Section: рис 2 динамика показателей гематокрита (%) в периоперационunclassified